Trilemma among energy, economic and environmental efficiency: Can dilemma of EEE address simultaneously in era of COP 21?. (15th December 2020) - Xia, Zhiqing; Abbas, Qaiser; Mohsin, Muhammad; Song, Ge
Abstract: Economic growth is a prerequisite for development while energy is the engine for growth process. In the era of globalization, production cost heavily dependent on energy intensity and efficiency with keeping environmental conditions intact. Therefore, the structuring of a significant environmental index is pre-requisition of the world with energy intensity, energy efficiency. For this objective, this study employs 18-years data set between 2000 and 2018 of Organization for Economic Co-operation and Development (OECD) to form a universal aspect of economics, environmental index, and energy efficiency (EEE). The data envelopment analysis (DEA) and arithmetic mean aggregation in the formation of mathematical aggregation mechanisms are applied for empirical analysis. According to the results, Iceland maintained an overall high rank regarding energy efficiency, energy intensity, and environment followed by Greece, New Zeeland, and Norway. In this investigation, Ireland followed by the UK and the USA are the lowest performer regarding energy and environment. Thus, the study concludes that energy (efficiency & intensity) and environment hold complex relations and needs a special set of policies to address them collectively and it is expected that this study can be used as valuable information for the policymaking process. Highlights: Dilemma of EEE (energy, economic, and environment) is very complex and sensitive. This Study investigates EEE by applying Slack-based DEA method given COP21. OECD countries are performing much better in the case of environmental efficiency. The condition of energy efficiency is mixed for OECD economies. These results are cross verified through sensitivity analysis.